The dynamics of capillary flow in an open-channel system featuring trigger valves - Jodie C. Tokihiro; Ingrid H. Robertson; Denise Gregucci; Albert Shin; Elisa Michelini; Tristan M. Nicholson; Ayokunle O. Olanrewaju; Ashleigh B. Theberge; Jean Berthier; Erwin Berthier (Scientific Reports)
Abstract Trigger valves are fundamental features in capillary-driven microfluidic systems that stop fluid at an abrupt geometric expansion and release fluid when there is flow in an orthogonal channel connected to the valve. The concept was originally demonstrated in closed-channel capillary circuits. We show here that trigger valves can be successfully implemented in open channels. We also show that a series of open-channel trigger valves can be placed alongside or opposite a main channel resulting in a layered capillary flow. We developed a closed form model for the dynamics of the flow at trigger valves based on the concept of average friction length and successfully validated the model against experiments. For the main channel, we discuss layered flow behavior in the light of the Taylor-Aris dispersion theory and in the channel turns by considering Dean theory of mixing. This work has potential applications in autonomous microfluidics systems for biosensing, at-home or point-of-care sample preparation devices, hydrogel patterning for 3D cell culture and organ-on-a-chip models.